A new class of stereoregular vinylene‐arylene copolymers with double‐decker silsesquioxane in the main chain. Issue 8 (12th November 2015) - Żak, Patrycja; Dudziec, Beata; Dutkiewicz, Michał; Ludwiczak, Monika; Marciniec, Bogdan; Nowicki, Marek
ABSTRACT: A synthesis of a new macromolecular class of vinylene‐arylene copolymers with double‐decker silsesquioxane in the main chain is presented. Two transition‐metal‐catalyzed processes, which is silylative‐coupling copolycondensation (SCC) and ADMET copolymerization of divinyl‐substituted double‐decker silsesquioxanes (DDSQ‐2SiVi) with selected diolefins, are reported to be highly efficient tools for the formation of stereoregular copolymers containing DDSQ‐silylene‐vinylene‐arylene units. The copolymeric products are studied in terms of their structural, thermal, and mechanical properties. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1044–1055 Abstract : A new class of stereoregular DDSQ‐silylene‐vinylene‐arylene copolymers with double‐decker silsesquioxane in the main chain were synthesized via complementary SCC and ADMET copolymerization reactions. The impact of reaction type, its duration, type of DDSQ‐2SiVi and diolefin on structure, thermal, and mechanical properties are studied.